Determinants of Bank’s Resilience in Emerging Market: SEM PLS Approach - Nugroho, Arif Widodo; Asrunputri, Aisyah Pia; Sumardi, Sumardi (Budapest International Research and Critics University, 2021)
The banking industry is one of the industries that plays a role in global economic conditions, thus the resilience of the Bank is very important. The purpose of this study was to determine the effect of Bank Competition, Good Corporate Governance (GCG), and Bank Performance on Bank Resilience in Emerging Market. This research is a quantitative study by taking bank data listed on the Indonesia Stock Exchange during 2015-2019. This study used panel data and applied regression analysis with the Structural Equation Modeling (SEM) approach. The findings state that only the Bank Performance was the only variable that is significant for Bank Resilience, while the other two variables were not significant.